2009
DOI: 10.1016/j.scr.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Generation of tissue-specific cells from MSC does not require fusion or donor-to-host mitochondrial/membrane transfer

Abstract: Human mesenchymal stem cells (MSC) hold great promise for cellular replacement therapies. Despite their contributing to phenotypically distinct cells in multiple tissues, controversy remains regarding whether the phenotype switch results from a true differentiation process. Here, we studied the events occurring during the first 120 h after human MSC transplantation into a large animal model. We demonstrate that MSC, shortly after engrafting different tissues, undergo proliferation and rapidly initiate the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 53 publications
1
50
0
2
Order By: Relevance
“…In some cases, such as the FAH model, it appears that the donor-derived hepatocytes are generated almost entirely through the process of cell fusion, in which the transplanted HSC fuse with the host’s endogenous hepatocytes, generating cells that morphologically and phenotypically appear to be hepatocytes, yet contain the DNA from both the donor HSC and the host hepatocytes [292, 307, 314]. In other models, including the non-injury fetal sheep model, the hepatocytes appear to be generated almost exclusively through what seems to be true reprogramming/trans-differentiation of the transplanted cells into hepatocytes without exchange of any genetic or cellular elements between the host and the engrafted human cells [293, 297, 306, 308, 315, 316]. Another important caveat is that the phenotype and purity of the cell population transplanted also plays a role in whether hepatocytes are generated and, if so, whether donor-host cell fusion occurs [317320].…”
Section: Hsc Transplantation For Diseases Of Non-hematopoietic Orgmentioning
confidence: 99%
“…In some cases, such as the FAH model, it appears that the donor-derived hepatocytes are generated almost entirely through the process of cell fusion, in which the transplanted HSC fuse with the host’s endogenous hepatocytes, generating cells that morphologically and phenotypically appear to be hepatocytes, yet contain the DNA from both the donor HSC and the host hepatocytes [292, 307, 314]. In other models, including the non-injury fetal sheep model, the hepatocytes appear to be generated almost exclusively through what seems to be true reprogramming/trans-differentiation of the transplanted cells into hepatocytes without exchange of any genetic or cellular elements between the host and the engrafted human cells [293, 297, 306, 308, 315, 316]. Another important caveat is that the phenotype and purity of the cell population transplanted also plays a role in whether hepatocytes are generated and, if so, whether donor-host cell fusion occurs [317320].…”
Section: Hsc Transplantation For Diseases Of Non-hematopoietic Orgmentioning
confidence: 99%
“…11 One possible therapeutic approach for treatment of immune mediated disorders is the use of mesenchymal stem cells (MSCs). MSCs are adult-derived stem cells that can be obtained from a variety of tissue sources including bone marrow 12,13 and adipose tissue. [14][15][16] Adipose-derived (Ad) MSCs have been isolated and characterized from several animal species including dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Using the fetal sheep model made it possible for us to show that MSC could give rise directly to cells within the liver without the need for first forming hematopoietic elements [41]. In more recent studies, we have now shown that the ability to directly contribute to liver repopulation without the need for a hematopoietic intermediate enables the transplanted MSC to rapidly begin contributing to the growing liver, producing cells with hepatic markers within as little as 24 or 48 hours post-transplantation [41].…”
Section: Results Obtained In Fetal Sheep Modelmentioning
confidence: 99%
“…In more recent studies, we have now shown that the ability to directly contribute to liver repopulation without the need for a hematopoietic intermediate enables the transplanted MSC to rapidly begin contributing to the growing liver, producing cells with hepatic markers within as little as 24 or 48 hours post-transplantation [41]. The findings of these more recent studies confirmed our prior findings regarding the lack of a need for fusion, and furthered our understanding of the mechanism of hepatic repopulation by demonstrating that the generation of hepatocytes occurs independently of the transfer of either mitochondria or membrane-derived vesicles between the transplanted donor cells and the cells of the recipient liver [41]. These findings thus provide strong evidence to support genetic reprogramming and differentiation of the transplanted stem cells.…”
Section: Results Obtained In Fetal Sheep Modelmentioning
confidence: 99%